GOOD GOVERNANCE IN PAKISTAN: CHALLENGES AND RECOMMENDATIONS - Muhammad Imran; Rohaida Nordin, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Good governance is necessary for human development and poverty elimination as it formsa well-functioning public sector that follows the standards of transparency, participation,ownership and accountability to civilians. It forms the transparent and accountable administrationof public resources that decrease corruption and ensure that public resources are utilised for thebenefit of all citizens in recognition of their fundamental rights. Good governance facilitates anunderstanding of civil, cultural, economic, social and political rights while holding leaders toaccount. Hence, good governance and human development are interlinked. This paper defines theconcept of good governance. It illustrates the elements necessary for good governance and identifiesthe problems of good governance in Pakistan. This paper demonstrates that bad governance inPakistan has created lawlessness, social, economic and political failure. This paper concludes withsuggestions to overcome the problems of bad governance in Pakistan.